DYRK1A interacts with histone acetyl transferase p300 and CBP and localizes to enhancers. Issue 21 (22nd August 2018) - Li, Shanshan; Xu, Chu; Fu, Yinkun; Lei, Pin-Ji; Yao, Yanhua; Yang, Wanli; Zhang, Ying; Washburn, Michael P; Florens, Laurence; Jaiswal, Manish; Wu, Min; Mohan, Man
Abstract: DYRK1A, dual-specificity tyrosine phosphorylation-regulated kinase 1A, which is linked to mental retardation and microcephaly, is a member of the CMGC group of kinases. It has both cytoplasmic and nuclear functions, however, molecular mechanisms of how DYRK1A regulates gene expression is not well understood. Here, we identify two histone acetyltransferases, p300 and CBP, as interaction partners of DYRK1A through a proteomics study. We show that overexpression of DYKR1A causes hyperphosphorylation of p300 and CBP. Using genome-wide location (ChIP-sequencing) analysis of DYRK1A, we show that most of the DYRK1A peaks co-localize with p300 and CBP, at enhancers or near the transcription start sites (TSS). Modulation of DYRK1A, by shRNA mediated reduction or transfection mediated overexpression, leads to alteration of expression of downstream located genes. We show that the knockdown of DYRK1A results in a significant loss of H3K27acetylation at these enhancers, suggesting that DYRK1A modulates the activity of p300/CBP at these enhancers. We propose that DYRK1A functions in enhancer regulation by interacting with p300/CBP and modulating their activity. Overall, DYRK1A function in the regulation of enhancer activity provides a new mechanistic understanding of DYRK1A mediated regulation of gene expression, which may help in better understanding of the roles of DYRK1A in human pathologies.